2002
DOI: 10.1128/aac.46.8.2458-2461.2002
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Rapidly Reaches All the Constituent Cells of Uropathogenic Escherichia coli Biofilms

Abstract: We have developed a method for visualizing Escherichia coli cells that are exposed to tetracycline in a biofilm, based on a previous report that liposomes containing the E. coli TetR(B) protein fluoresce when exposed to this antibiotic. By our method, cells devoid of TetR(B) also exhibited tetracycline-dependent fluorescence. At 50 g of tetracycline ml؊1 , planktonic cells of a uropathogenic E. coli (UPEC) strain developed maximal fluorescence after 7.5 to 10 min of exposure. A similar behavior was exhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 18 publications
2
59
1
1
Order By: Relevance
“…The same observation was made concerning K. pneumoniae biofilms and ciprofloxacin (22). Studies using fluorescent tetracycline demonstrated that 2-day biofilms were less susceptible than planktonic bacteria, whereas tetracycline-mediated fluorescence was present throughout the biofilm within 10 min (47). On the other hand, delayed antibiotic penetration may have important phenotypic consequences.…”
Section: Biofilm Recalcitrance Is Multifactorialsupporting
confidence: 53%
“…The same observation was made concerning K. pneumoniae biofilms and ciprofloxacin (22). Studies using fluorescent tetracycline demonstrated that 2-day biofilms were less susceptible than planktonic bacteria, whereas tetracycline-mediated fluorescence was present throughout the biofilm within 10 min (47). On the other hand, delayed antibiotic penetration may have important phenotypic consequences.…”
Section: Biofilm Recalcitrance Is Multifactorialsupporting
confidence: 53%
“…The unaltered MIC indicates that the kanamycin resistance of the invading populations is caused by an adaptive mechanism conferring phenotypic resistance, instead of being genetically encoded. Most previously described antibiotic-tolerant phenotypes are based on dormancy (Balaban et al, 2004;Lewis, 2010;Fridman et al, 2014) or reported the transient resistance of matured biofilms that were formed in the absence of antibiotics and exposed only after maturation (Spoering and Lewis, 2001;Anderl et al, 2000;Stone et al, 2002;Amini et al, 2011;Nguyen et al, 2011;Kirby et al, 2012). In contrast, the density-dependent adaptive resistance observed here enables planktonic E. coli to found a population in an antibiotic landscape, and permits swimming motility and population expansion in the presence of a lethal concentration of the antibiotic.…”
Section: Resultsmentioning
confidence: 74%
“…1,2 For example, in a rabbit model of CAUTI, 400 mg/kg of amdinocillin was required to eliminate Escherichia coli from the surface of the urinary catheter, although the minimum inhibitory concentration of amdinocillin against this organism in the planktonic state was 0.5 μg/mL. 13 Because several studies show that antibiotics can penetrate mature biofilms thoroughly, [14][15][16] the slow growth rates of organisms in biofilms is probably the major factor in conferring resistance. In addition, the juxtaposition of microorganisms of 1 or more species within a biofilm facilitates the transfer of antimicrobial resistance genes.…”
mentioning
confidence: 99%